Associação entre os níveis plasmáticos de ácido hialurônico e colágeno IV e o grau de fibrose hepática em portadores do vírus da hepatite c e doença renal crônica em hemodiálise - Renata Eliane de Avila (2007)
The importance of hyaluronic acid (HA) and collagen IV (C-IV) in the evaluation of liver fibrosis in patients with chronic hepatitis C on haemodialysis has yet to be defined. Herein we describe a study devised to fill out this gap. Seventy six subjects attending the Centro de Treinamento e Referencia em Doencas Infecciosas e Parasitarias/Secretaria Municipal de Saude de Belo Horizonte/ Universidade Federal de Minas Gerais (UFMG) and the Centro deDialise do Hospital das Clinicas da UFMG, Brazil, from May 2000 to September 2007 have been selected for this study. Patients were categorized into three groups: Group 1: patients with hepatitis C and chronic renal disease (CRD) undergoing haemodialysis (CRD/ hepatitis C, n = 23); Group 2: patients with hepatitis C, without CRD (hepatitis C, n = 29); Group 3: patients with chronic renal disease (CRD) undergoing haemodialysis without hepatitis C (CRD, n = 24). A protocol with socio-demographic, clinical and laboratory data was completed by the subjects enrolled in this study. Plasma levels of HA and C-IV were measured by an enzyme-linked immunosorbent assay (ELISA) using a commercial kit. In Groups 1 (CRD/ hepatitis C) and 2 (hepatitis C) the HA and C-IV levels were correlated with the histological data of the fragments obtained by liver biopsy. Histological analyses were performed by the Servico de Anatomia Patologica da Faculdade de Medicina da UFMG. METAVIR group scoring system was used for the classification of the histological findings. Fibrosis was categorized into two stages: METAVIR < F2 (absent or mild) and METAVIR . F2 (significant). The three groups were similar regarding gender, race, schooling, blood transfusion history and the use of illicit drugs. In Group 3, the mean age was lower whencompared to other groups. HA plasma level was a good marker of liver fibrosis in Groups 1 and 2. Higher plasma levels were significantly correlated to liver fibrosis METAVIR . F2. In group 1, the HA cutoff to discriminate significant fibrosis was 984, 8 ng/mL, with sensitivity and specificity of 83% and 70%, respectively. In Group 2, the HA cutoff was 222, 3 ng/mL, with sensitivity and specificity of 70% and 94%, respectively. No correlation was observed in C-IV plasma level and the degree of liver fibrosis. Age, gender and duration of haemodialysis were significantly correlated to HA serum levels in patients with CRD.Summing up, HA was a good marker of liver fibrosis in patients with hepatitis C on haemodialysis and, thence, may help the physician to decide the best moment to treat hepatitis C in patients with chronic renal disease.